Early Marriage in Medical View and Maqashid Sharia - Rifanto Bin Ridwan; Ifnaldi Ifnaldi; Jahidin Jahidin (AJIS: Academic Journal of Islamic Studies, 2021)
This article aims to find out how the medical and legal views of Islam (Maqashid Sharia) on marriages are carried out by minors. Through library research methods, this study found; 1) from a medical point of view, early marriage is not recommended. Because it can harm the reproductive health of women who are still in their infancy. Mentally, the perpetrators will feel inferior and less able to control their emotions due to emotional unpreparedness, 2) in terms of Maqashid Sharia, early marriage should be avoided. Because, although the goal of Sharia, namely maintaining offspring, is fulfilled, in practice it often causes problems, so that the purpose of marriage, which is getting sakinah mawaddah wa rahmah, is not achieved